Serum cystatin C for evaluation of acute kidney injury in adults treated with colistin - Rozina Abbasi Larki; Bahareh Jamali; Mohsen Meidani; Sarah Mousavi (Wolters Kluwer Medknow Publications, 2018)
Objective: Recent studies have shown that serum cystatin C (Cys C) is a better marker for measuring the glomerular filtration rate and may rise more quickly with acute kidney injury (AKI). The purpose of this study was to evaluate the clinical application of serum Cys C to predict colistin-induced nephrotoxicity in comparison with serum creatinine (SCr). Methods: Thirty-two adult patients with no history of acute or chronic kidney injury having been planned to receive intravenous colistin for an anticipated duration of at least 1 week for any indication were recruited. At baseline and 5 days after colistin treatment, serum Cys C as well as creatinine levels were measured. The incidence of colistin-induced acute renal failure was defined according to the AKIN criteria for SCr. Rise in concentration of Cys C by more than 10% from baseline considered as AKI. Findings: Colistin-induced nephrotoxicity (defined as SCr ≥0.3 mg/dl) occurred in 6 patients (18.8%). A Cys C increase concentration ≥10% after 5 days of colistin treatment was detected in 15 patients (46.9%). There was a poor agreement between the presence and absence of any SCr-AKI and Cys C-AKI (κ = 0.28, P = 0.04). Conclusion: Serum Cys C is a better marker of renal function in early stages of AKI and predictive of persistent AKI on colistin treatment.